Pharmacotherapy of Depression - Ciraulo, Domenic A.; Shader, Richard Irwin; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Comprehensive and state-of-the-art, the second edition of Pharmacotherapy of Depression offers major revisions of every chapter and the addition of new chapters by expert contributors. The first chapter reviews the neurobiology of depression, which lays the groundwork for understanding the mechanisms of action of antidepressants. In the next chapter, a review of the general principles guiding the diagnosis and medication treatment of unipolar depression is provided. The clinical pharmacology of antidepressants is reviewed in some detail, supplemented by tables that provide information on dosing, indications, and metabolism. Augmentation strategies are reviewed, including the use of non-traditional agents. The chapters that follow next address the use of antidepressants in special populations, such as the elderly and depressed individuals with psychosis, bipolar disorder, substance abuse, and post traumatic stress disorder. The complex issues involving the diagnosis and treatment of depression during pregnancy is thoroughly reviewed in Chapter 8 and provides a synthesis of the scientific literature in the area, one that is noted for contradictory and controversial findings, as well as guidelines for prescribing. The next chapter then provides an overview of the treatment of depression in the pediatric population, highlighting clinical concerns such as suicide risk. The book concludes with two chapters at the interface of medicine and psychiatry in the treatment of mood disorders: managing depression in primary care settings and depression associated with medical illnesses. The outstanding clinician-scientists who have contributed to this volume are all leaders in their fields and represent a broad spectrum of renowned institutions. A timely contribution to the literature, The Pharmacotherapy of Depression, Second Edition, offers busy clinicians from many disciplines a strong scientific foundation that seamlessly transitions into practical recommendations for clinical practice. The result is another gold-standard guide to the safe and effective use of the latest antidepressant medications.
1. Biological Theories of Depression and Implications for Current and New Treatments -- 2. Clinical Pharmacology and Therapeutics of Antidepressants -- 3. Antidepressant Treatment of Geriatric Depression -- 4. Treatment of Psychotic Disorders -- 5. Treatment of Biploar Depression -- 6. Substance Abuse and Depression -- 7. Antidepressant Treatments in Posttraumatic Stress Disorder -- 8. Diagnosis and Treatment of Depression During Pregnancy and Lactation -- 9. Antidepressant Treatment of Pediatric Depression -- 10. Managing Depression in Primary Care -- 11. Treatment of Depression in the Medically Ill.
Keywords: Medicine; Family medicine; Internal medicine; Psychiatry; Philosophy (General).; Medicine & Public Health; Psychiatry; Psychology, general; General Practice / Family Medicine; Internal Medicine